MAKANAN ADAT PADA ACARA MANANTI MARAPULAI DI KELURAHAN CAMPAGO GUGUAK BULEK KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Jannah, Annisa Miftahul; Baidar, Baidar; Elida, Elida (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of this study was to describe the implementation of a series ofevents mananti marapulai, identify the types of tradisional food, describe theequipment used for served and present food customs, expresses the meaning ofthe food served at the event mananti marapulai. In the study used a qualitativestudy with a descriptive approach, the object of study is the food served at theevent mananti marapulai in Kelurahan Campago Guguak Bulek. The techniqueof collected data through observasion, interviews and documentation. Dataanalysis techniques: data reduction, data presentation and conclusion orverification.The results showed that mananti marapulai consists of two stege,thepreparation befor the event and the circuit implementation. Tradisional foodsserved at eight types. Equipment used for served and present is pinggan, piriangmakan, piriang samba, cambuang basuah, galeh and talam. Tradisional food theevent mananti marapulai has the meaning of the family life and life at both sidesof the family